Model of Resilience for Caring Enhancement (More Care) Module Implementation Improves Caring Behavior of ICU Nurses - Dewi, Yulis Setiya; Nursalam, Nursalam; Hargono, Rachmat (International Journal of Psychosocial Rehabilitation, 2020)
The ICU is a ward with high stress levels and nurses experience stress at various levels. However, study to improve nursing caring behavior is limited particularly in ICU in Indonesia. This study was performed to reveal whether implementation of the More Care (model of resilience for caring enhancement) Module was effective to improve nurses’ caring behavior in a referral hospital in Surabaya Indonesia. This research used a quasi-experimental design with a pre-test –post-test control group design. The respondents were 30 ICU nurses who were obtained using a purposive sampling technique, divided into two groups of 15 for each control and intervention group. The dependent variable was caring behavior of ICU nurses while the independent variable was implementation of the More Care Module. The implementation of the module using in-house training was given for 4 weeks. The data were analyzed using a t test, Mann Whitney and Wilcoxon Test based on the normality test of the data. The study findings revealed that the implementation of the module increased significantly the caring behavior (p = 0.001) for the intervention group but not for the control group (p = 0.106). The result also showed significant differences in the post-test of the two groups (0.000). The More Care Module improves the caring behavior of ICU nurses. Caring behavior of nurses is important to ensure the patients’ satisfaction as well as nurses’ satisfaction. Nursing management may provide training on caring behavior regularly.